International Migration in Sub-Saharan Africa: A Call for a Global Research Agenda (African Human Mobility Review, 2021)
Research on international migration has brought about remarkable awareness within the global research community, stimulating some theorists and policy-makers to talk about ‘international migration’ as a field for research. A number of research organizations have also adopted various methods of inquiry to examine and change their research agendas and practices. Although much is known about international migration, there are still many unanswered questions. Formulating a comprehensive agenda that is well informed by research can have a real influence on the lives of migrants throughout the world. It is also believed that the outcome of this research will help the ways in which concerned organizations think and act while dealing with the situation of international migrants. This research is aimed at drawing an inclusive research agenda that is better informed by distinguishable human rights requirements. The research agenda presented here is the result of the contribution of nearly 35 purposely selected researchers from various organizations working in the area of international migration in sub-Saharan Africa. The knowledge base that is produced from this study can yield data and information to governmental and non-governmental organizations that are dealing with international migration in sub-Saharan Africa.